Fenomena Kebernyawaan dalam Bahasa Arab - Namira Az-Zahra; Mulyadi Mulyadi (STIQ Amuntai, 2026)
This research aims to examine how animacy operates in the Arabic grammatical system by analyzing various linguistic phenomena that reflect an animacy hierarchy in sentence structure. This research is literature research using a qualitative approach. The data in this study consist of Arabic sentences that use the concept of animacy. The data sources include various documents, including books, dictionaries, articles, and scientific journals, related to the phenomenon of animacy in Arabic. Data collection techniques involve documenting data sources. The research finds that animacy is one of the features that strongly influence the grammatical system of Arabic, including subject-predicate agreement, the use of pronomina, the selection of relative conjunctions (ism mawṣūl), the formation of plurals, and strategies to avoid ambiguity. Animacy is not only a marker of meaning but also manifests itself across various linguistic structures, reflecting an animacy hierarchy that regulates the relationships among form, meaning, and function in sentences.